Computation of the scattering from inhomogeneous objects with a discrete rotational symmetry and a nonsymmetric part. - Soudais, P. (IEEE Transactions on antennas and propagation)
Using a specific solver for circulant matrices can reduce the cost of computing the scattering from a discrete rotational symmetric object by up to several orders of magnitude. A solver is developed for symmetric objects with a nonsymmetrical part (such as an antenna on a body of revolution). This solver has been implemented in a finite-element code based upon a hybrid formulation. The hybrid formulation combines integral equations and partial differential equations; it can handle inhomogeneous anisotropic objects of arbitrary shape. Results on inhomogeneous objects with defects are shown. The solver can also be used to perform a parametric study of the defects